Strain energy release rate determination of stress intensity factors by finite element methods - Walsh, Richard Michael; Byron Pipes, R. (Engineering fracture mechanics, 1985)
The determination of the Mode I stress intensity factors for selected crack configurations, using finite element methods and energy release rate principles, is the subject of this study. The crack configurations which were investigated are the double edge crack, the single edge crack and the center crack. The method of analysis utilized was the “Stiffness Derivative Method.” This approach relates the change in strain energy resulting from crack advancement, to the change in the stiffness matrix of the structure containing the crack. The results indicated that through mesh optimization and proper control of certain parameters including the crack advance increment, the crack tip element contour size and mesh refinement, an accurate solution can be calculated with a relatively coarse finite element mesh consisting entirely of contemporary elements. The numerically generated solutions are compared with analytical solutions with the results within 0.001% of each other for the double edge crack, 0.858% for the single edge crack and 2.021% for the center crack.